The changing legitimacy of health and safety, 1960–2015: understanding the past, preparing for the future. Issue 1 (2nd January 2016) - Almond, Paul; Esbester, Mike
Abstract: 'Health and safety' currently has an image problem in the UK. This article explores the origins of these current negative perceptions, framed around the concept of legitimacy – the degree to which a policy project of this sort is viewed as right, proper, and appropriate. The article considers and evaluates key moments in the growth and decline of social consensus around health and safety since 1960, including the Robens Committee and subsequent Health and Safety at Work Act, the decline of trade unionism, the extension of health and safety beyond the workplace, and the rise of the safety profession. It concludes that change has been much more subtle and less uniform than general perceptions might suggest, and makes recommendations for how public engagement with occupational health and safety might be restructured.